Impact of (virtual) set-up errors on DVH dose results in IMRT plans for head-neck cancer. (September 2016) - Armpilia, C.; Zygogianni, A.; Avgousti, R.; Apostolou, E.; Nikolakopoulou, A.; Antypas, C.
Abstract : Introduction-purpose: The aim of this study is to evaluate the impact of isocenter shift in three directions (lateral, longitudinal and vertical) on DVH results in IMRT plans for head and neck cancer treatment, in order to simulate possible set-up errors and its effects on treatment outcome. Materials and methods: IMRT step and shoot plans for ten patients with head and neck cancer were created on the Oncentra TPS according to RTOG 0615 protocol. Three PTVs were outlined with prescribed dose of 54 Gy (PTV54), 59.4 Gy (PTV59.4) and 70 Gy (PTV70) in 33 fractions. Each treatment plan was recalculated for isocenter shift of ±3 mm in all directions. DVHs were regenerated for PTVs and critical structures for all shifted plans. Results: Mean values of V51.3, V57 and V66.5 were calculated in standard plan for PTV54, PTV59.4 and PTV70 as 95.3 (SD = 1.3), 93.5 (SD = 0.9 and 95.3 (SD = 1.8) respectively. The maximum deviation n PTV70 coverage was found in the posterior direction 5% less than the standard plan value. Both PTV59.4 and PTV50 showed a decrease in coverage within a range of 4–8% either in the anterior or in the longitudinal direction. The mean D2 values calculated for spinal cord and brainstem for the standard plan were 42.0 Gy (SD = 2.1) and 42.6 Gy (SD = 2.1) respectively. The greatest deviation for shifted plans was found in the posterior direction 11% more than the standard (no shift) value. The average D50 for left and right parotids were 26.4 Gy (SD = 1.2) and 27 Gy (SD = 1.3) respectively. The greatest deviation was found reciprocally in the lateral direction 13% less than the standard plan value. Conclusion: In this study, isocenter shift of ±3 mm reveals significant deviations of calculated DVH parameters. Such possible set-up errors could result in non-adequate PTV coverage and in dose values for critical structures outside of compliance criteria. These results indicate the importance of daily IGRT and subsequent patient setup correction for efficient IMRT treatment outcome.